14‐3‐3 and β‐catenin are secreted on extracellular vesicles to activate the oncogenic Wnt pathway. Issue 5 (22nd March 2014) - Dovrat, Shiri; Caspi, Michal; Zilberberg, Alona; Lahav, Lital; Firsow, Anastasia; Gur, Hila; Rosin-Arbesfeld, Rina
Abstract : Aberrant activation of the canonical Wnt signal transduction pathway is involved in a large number of human diseases. β‐catenin, the key effector protein of the canonical Wnt pathway, functions in the nucleus with T‐cell factor/lymphoid enhancer factor (TCF/LEF) to activate expression of Wnt target genes. Here we show that members of the 14‐3‐3 protein family bind disheveled‐2 (Dvl‐2) and glycogen synthase‐3β (GSK‐3β) to attenuate the interaction between GSK‐3β and β‐catenin. Importantly, 14‐3‐3 and β‐catenin form "bleb‐like" structures and are secreted via extracellular vesicles to induce Wnt signaling activity in target cells. Our data suggest a novel way of transducing the oncogenic Wnt signal in which β‐catenin is regulated by 14‐3‐3ζ through the formation of "oncosomes" that contain both the 14‐3‐3 and β‐catenin proteins. Highlights: A controversy exists regarding the role of the 14‐3‐3 proteins and the oncogenic Wnt pathway. 14‐3‐3 activates the pathway through interaction with a number of Wnt signaling components. 14‐3‐3 and β‐catenin form "bleb‐like structures". 14‐3‐3 and β‐catenin transmit the oncogenic signal via extracellular vesicles.